2021
DOI: 10.1038/s41467-021-21774-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD318, TSPAN8 and CD66c as target candidates for CAR T cell based immunotherapy of pancreatic adenocarcinoma

Abstract: A major roadblock prohibiting effective cellular immunotherapy of pancreatic ductal adenocarcinoma (PDAC) is the lack of suitable tumor-specific antigens. To address this challenge, here we combine flow cytometry screenings, bioinformatic expression analyses and a cyclic immunofluorescence platform. We identify CLA, CD66c, CD318 and TSPAN8 as target candidates among 371 antigens and generate 32 CARs specific for these molecules. CAR T cell activity is evaluated in vitro based on target cell lysis, T cell activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 75 publications
1
52
0
Order By: Relevance
“…In pancreatic cancer, CD8-positive cytotoxic T cells are associated with better prognosis [ 33 , 34 ]. A variety of therapies have been tested to increase CD8 T cell infiltration into the stroma of PDAC, including chimeric antigen receptor T cell therapies, CD40 antibody blockade, and CCL2/CCR2 blockade [ 35 , 36 , 37 , 38 ]. Additionally, depletion of immunosuppressive cells in the tumor microenvironment of PDAC including T regulatory cells, tumor-associated dendritic cells, and MDSCs have been shown to increase CD8 cell infiltration [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, CD8-positive cytotoxic T cells are associated with better prognosis [ 33 , 34 ]. A variety of therapies have been tested to increase CD8 T cell infiltration into the stroma of PDAC, including chimeric antigen receptor T cell therapies, CD40 antibody blockade, and CCL2/CCR2 blockade [ 35 , 36 , 37 , 38 ]. Additionally, depletion of immunosuppressive cells in the tumor microenvironment of PDAC including T regulatory cells, tumor-associated dendritic cells, and MDSCs have been shown to increase CD8 cell infiltration [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…After re-analyzing the co-expression of these markers, we concluded that an AND gated target combination of CDCP1 with TSPAN8 or CEACAM6 could be promising from a safety perspective of a CAR T cell therapy (Fig. 6 ), while development of CLA-specific CAR T cells requires further technical solutions as it is expressed on activated CAR T cells 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Using a similar approach as described above, we previously reported the analysis of PDAC 17 . There we identified CDCP1 (CD318), tetraspanin-8 (TSPAN8), cutaneous lymphocyte-associated antigen (CLA) and CEACAM6 (CD66c) as target candidates for CAR T cell-based immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…After re-analyzing the co-expression of these markers, we concluded that an AND gated target combination of CDCP1 with TSPAN8 or CEACAM6 could be promising from a safety perspective of a CAR T cell therapy (Fig. 6), while development of CLA speci c CAR T cells requires further technical solutions as it is expressed on activated CAR T cells 17 . Finally, we applied our screening approach to HGSOC.…”
Section: Mics Reveals Novel Pairs Of Surface Proteins As Candidates For Car T Based Immune Therapiesmentioning
confidence: 99%
“…Using a similar approach as described above, we previously reported the analysis of PDAC 17 . There, we identi ed CDCP1 (CD318), tetraspanin-8 (TSPAN8), cutaneous lymphocyte-associated antigen (CLA) and CECAM6 (CD66c) as target candidates for CAR T cell based immunotherapy.…”
Section: Mics Reveals Novel Pairs Of Surface Proteins As Candidates For Car T Based Immune Therapiesmentioning
confidence: 99%